Privately protected areas in Mexico, a 2012–2023 update - Bezaury-Creel, Juan E. (Frontiers in Conservation Science, 2024)
Privately protected areas (PPAs) in the modern sense have been established over the last 50 years in Mexico. In 2002 the first PPA was legally "certified" by the Mexican government. The last PPA country review used data from 2012, so a decadal update is considered to be timely. By June 2023, 546 land parcels within 27 states held valid certificates as PPAs or ICCAs, for a total of 718,526 hectares (ha). PPAs include 175,006 ha of private lands plus 9,860 of public property, which jointly represents a 44 % increase from their 2012 coverage of 128,369 ha, while community lands or "territories and areas conserved by indigenous peoples and local communities" (ICCAs) now comprise 486,082 ha. No new uncertified PPA inventory has been developed to date, but their number and territorial coverage has uncreased. After more than 20 years of use of the certified "voluntary conservation use areas" (ADVC) mechanism, this review gives us a clearer and more mature picture of the benefits and limitations of using this legal tool. For example, no 10 year -the initial minimum required by law -certificates remain. Meanwhile the Kunming-Montreal Global Biodiversity Framework´s 30x30 target, emphasis on effectively conserved and managed areas has resulted in the developing of an ADVC assessment tool, while advances towards the establishment of a legal "easement in gross" mechanism, through contractual means has been developed for one This is a provisional file, not the final typeset article Mexican state, which will serve as a proof concept precedent for other states. Overall certification of ADVCs has proved to be a useful tool for conservation of biodiversity and environmental services, which certainly needs to evolve to become more effective and efficient, in order to be a more widely used tool and increase its contribution for achieving Targe 3 of the Kunming-Montreal Global Biodiversity Framework for México.